Stan polskiej demokracji lokalnej w świetle standardów Rady Europy i mechanizmu kontroli przestrzegania Europejskiej Konwencji Samorządu Terytorialnego – aspekty polityczne - Mirosław Natanek (Ksiegarnia Akademicka Publishing, 2020)
The Condition of Local Democracy in Poland in Light of the Council of Europe’s Standards and the European Charter of Local Self-Government Compliance Monitoring Mechanism. A Political Dimension